Meme Culture and Social Critique: Representations of Politics, Religion, and Nationalism in Indonesian Cyberspace - Firayani, Firayani (Kamara Journal, 2025)
This study analyzes how meme culture in Indonesian cyberspace represents and critiques politics, religion and nationalism through multimodal visual expressions. Using a qualitative approach grounded in multimodal critical discourse analysis, the research examines symbolic structures, intertextual cues and discursive functions embedded within widely circulated memes. Findings indicate that political memes act as vernacular tools for challenging authority, expressing dissatisfaction with governance and constructing alternative political narratives. Religious memes blend sacred symbolism with humor, enabling youth to renegotiate moral expectations and religious identity within digital environments. Nationalistic memes simultaneously reinforce patriotic sentiment and critique institutional shortcomings, revealing ambivalent relationships between civic pride and political frustration. Across these domains, meme culture facilitates both playful political participation and antagonistic discourse, sometimes escalating polarization through humor mediated hostility. The integrated analysis demonstrates that memes operate as cultural artifacts that shape public interpretation of sociopolitical events by simplifying complex issues into accessible visual rhetoric. Memes thus function not only as entertainment but also as influential discursive instruments within Indonesia’s digital public sphere. Future research should explore demographic variations in meme interpretation and the algorithmic dynamics that shape meme visibility in online platforms.